Traffic-related air pollution and APOE4 can synergistically affect hippocampal volume in older women: new findings from UK Biobank - Popov, Vladimir A.; Ukraintseva, Svetlana V.; Duan, Hongzhe; Yashin, Anatoliy I.; Arbeev, Konstantin G. (Frontiers in Dementia, 2024)
A growing research body supports the connection between neurodegenerative disorders, including Alzheimer's disease (AD), and traffic-related air pollution (TRAP). However, the underlying mechanisms are not well understood. A deeper investigation of TRAP effects on hippocampal volume (HV), a major biomarker of neurodegeneration, may help clarify these mechanisms. Here we explored TRAP associations with the HV in older participants of the UK Biobank (UKB), taking into account the presence of APOE e4 allele (APOE4), the strongest genetic risk factor for AD. Exposure to TRAP was approximated by the distance of the participant's main residence to the nearest major road (DNMR). The left/right HV was measured by magnetic resonance imaging (MRI) in cubic millimeters (mm 3 ). Analysis of variance (ANOVA), Welch test, and regression were used to examine statistical significance. We found significant interactions between DNMR and APOE4 that influenced HV. Specifically, DNMR less than 50 meters (equivalent of a chronically high exposure to TRAP), and carrying APOE4 were synergistically associated with a significant (P-value=0.01) reduction in the right HV by about 2.5% in women aged 60-75 years (results for men didn't reach a statistical significance). Results of our study suggest that TRAP and APOE4 jointly promote neurodegeneration in women. Living farther from major roads may help reduce the risks of neurodegenerative disorders, including AD, in female APOE4 carriers.